2019
DOI: 10.1111/tbed.13433
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for multiple recombination events within foot‐and‐mouth disease viruses circulating in West Eurasia

Abstract: Phylogenetic studies on foot‐and‐mouth disease viruses (FMDVs) circulating in the West Eurasian region have largely focused on the genomic sequences encoding the structural proteins that determine the serotype. The present study has compared near‐complete genome sequences of FMDVs representative of the viruses that circulate in this region. The near‐complete genome sequences (ca. 7,600 nt) were generated from multiple overlapping RT‐PCR products. These amplicons were from FMDVs belonging to serotypes O, A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 74 publications
4
27
0
Order By: Relevance
“…Again, we found that, although not absolute, Euro-Asiatic FMDVs tended to cluster together separately from the SAT stains (> 97% bootstrap support). However, in stark contrast to what we observed in the P1 tree, serotypes A, O, C and Asia1 appeared to intermix with one another in all of these trees, consistent with previous results 33 . Furthermore, a similar pattern was also found for the SAT1-3 serotypes.…”
Section: Recombination Detectionsupporting
confidence: 91%
See 2 more Smart Citations
“…Again, we found that, although not absolute, Euro-Asiatic FMDVs tended to cluster together separately from the SAT stains (> 97% bootstrap support). However, in stark contrast to what we observed in the P1 tree, serotypes A, O, C and Asia1 appeared to intermix with one another in all of these trees, consistent with previous results 33 . Furthermore, a similar pattern was also found for the SAT1-3 serotypes.…”
Section: Recombination Detectionsupporting
confidence: 91%
“…As previously noted, only a few recombination events were detected in the P1 region, which codes for capsid protein subunits [15][16][17][18][19] . A previous study of serotype O, A, and Asia-1 FMDVs circulating in West Eurasia also showed that, while the VP1-3 phylogenies were the same, a phylogeny estimated from the VP4 coding region was different from the rest 33 . This finding was consistent and further supported that the VP4 region is a recombination hotspot, and that the VP1-3 regions share the same evolutionary history.…”
Section: Recombination Detectionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, inter-lineage divergence in the VP2 region of African (5.4%) and Asian (3.9%) topotypes was the highest and the lowest lineage level divergence for serotype A. This difference in divergence among lineages within the same serotype may possibly be due to the recombination events in FMDVs within the conserved region of VP2 as described by Jamal et al (40,41). Importantly, at each hierarchical level, the divergence values for VP2 were lower than those for VP1, except the sub-lineage-level divergence of A/IRN-05 lineage where the values were equal.…”
Section: Discussionmentioning
confidence: 61%
“…This is challenging not only because there are seven immunologically distinct serotypes of FMDV: O, A, C, Asia 1 and Southern African Territories (SAT) 1, SAT 2, SAT 3. Like many RNA viruses, FMDV has high genetic variability, caused by error-prone RNA replication and extensive intra-and inter-serotype recombination [1,5]. Within each serotype, the many subtypes and lineages are evolving rapidly and are spread within and between known epidemiological clusters (so-called virus pools) by trade in live animals and animal products [1].…”
Section: Introductionmentioning
confidence: 99%